Rapid Dot-Blot Immunoassay for Detecting Multiple Salmonella enterica Serotypes - Cho, Jeongik; Song, Heymin; Yoon, Hyun C.; Yoon, Hyunjin (Journal of Microbiology and Biotechnology, 2024)
Salmonella, a major contributor to foodborne infections, typically causes self-limiting gastroenteritis. However, it is frequently invasive and disseminates across the intestinal epithelium, leading to deadly bacteremia. Although the genus is subdivided into >2,600 serotypes based on their antigenic determinants, only few serotypes are responsible for most human infections. In this study, a rapid dot-blot immunoassay was developed to diagnose multiple Salmonella enterica serotypes with high incidence rates in humans. The feasibility of 10 commercial antibodies (four polyclonal and six monoclonal antibodies) was tested using the 18 serotypes associated with 67.5% Salmonella infection cases in the United States of America (U.S.A) in 2016. Ab 3 (polyclonal; eight of 18 serotypes), Ab 8 (monoclonal; 13 of 18 serotypes), and Ab 9 (monoclonal; 10 of 18 serotypes) antibodies exhibited high detection rates in western blotting and combinations of two antibodies (Ab 3+8, Ab 3+9, and Ab 8+9) were applied to dot-blot assays. The combination of Ab 3+8 identified 15 of the tested 18 serotypes in 3 h, i.e., S. Enteritidis, S. Typhimurium, S. Javiana, S. I 4,[5],12:i:-, S. Infantis, S. Montevideo, S. Braenderup, S. Thompson, S. Saintpaul, S. Heidelberg, S. Oranienburg, S. Bareilly, S. Berta, S. Agona, and S. Anatum, which were responsible for 53.7% Salmonella infections in the U.S. in 2016. This cost-effective and rapid method can be utilized as an on-site colorimetric method for Salmonella detection.
Keywords: Humans; Immunoblotting; Salmonella; Salmonella enterica; Salmonella Infections; Serogroup; Serotyping; detection; dot-blot; Salmonella; serotype